Comparison of a Rabbit Model of Bacterial Endocarditis and an In Vitro Infection Model with Simulated Endocardial Vegetations - Hershberger, Ellie (American Society for Microbiology, 2000)
Animal models are commonly used to determine the efficacy of various antimicrobial agents for treatment of bacterial endocarditis. Previously we have utilized an in vitro infection model, which incorporates simulated endocardial vegetations (SEVs) to evaluate the pharmacodynamics of various antibiotics. In the present study, we compared four experimental rabbit endocarditis protocols to an in vitro infection model in an effort to determine if these models are comparable. We have evaluated the activity of clinafloxacin, trovafloxacin, sparfloxacin, and ciprofloxacin in rabbit models against Staphylococcus aureus and Enterococcus spp. In vitro models were performed simulating the antibiotic pharmacokinetics obtained in the in vivo studies. Models were dosed the same as rabbit models, and SEVs were evaluated at the same time the rabbit vegetations were examined. Clinafloxacin and trovafloxacin were evaluated against methicillin-susceptible (MSSA1199) and -resistant (MRSA494) strains of S. aureus. Ciprofloxacin was studied against MSSA1199 and MSSA487. Sparfloxacin and clinafloxacin were evaluated against Enterococcus faecium SF2149 and Enterococcus faecalis WH245, respectively. We found that reductions in SEV bacterial density obtained in the in vitro model were similar to those obtained in rabbit vegetations, indicating that the SEV model may be a valuable tool for assessing antibiotic potential in the treatment of bacterial endocarditis.